Hydatidiform Mole Complicated by Gestational Hyperthyroidism in a 9- Week Pregnancy (G6P4A1): A Case Report - Aliyyu Halin; Maulina Fita; Syanty Darma; Margaretha Margaretha (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Gestational trophoblastic disease is an abnormal form of pregnancy characterized by excessive proliferation of trophoblastic tissue, with hydatidiform mole being the most common presentation. Gestational hyperthyroidism is a rare but clinically significant complication resulting from markedly elevated β-human chorionic gonadotropin (β-hCG) levels that stimulate thyroid hormone production. Objective: To report a case of a complete hydatidiform mole complicated by gestational hyperthyroidism and to highlight the importance of early diagnosis. and appropriate management. Methods This study presents a case report of a 40-year-old woman (G6P4A1) at 9 weeks of gestation who presented with vaginal bleeding, hyperemesis, and palpitations. Clinical examination, laboratory investigations, ultrasonography, and histopathological analysis were performed to establish the diagnosis. Ultrasonography demonstrated a characteristic honeycomb appearance consistent with a complete hydatidiform mole. Laboratory findings revealed suppressed thyroid-stimulating hormone (TSH) levels and elevated thyroxine (T4) levels, indicating gestational hyperthyroidism. The diagnosis was confirmed by histopathological examination following uterine evacuation. The patient was managed with antithyroid medications, beta-blockers, preoperative stabilization, and suction curettage, resulting in a favorable clinical outcome. Conclusion: A complete hydatidiform mole may be associated with gestational hyperthyroidism due to excessive β-hCG production. Early recognition and comprehensive management are essential to prevent maternal complications. Recommendation: Routine assessment of thyroid function should be considered in patients with suspected or confirmed hydatidiform mole to optimize maternal outcomes.